Effect of fatty liver disease on liver function and fibrosis in patients with chronic hepatitis B: a cross-sectional study - Fang, Xiaohui; Yin, Yuhang; Zhao, Haonan; Wang, Cai’e; Li, Hui; Shang, Yiyang; Li, Jiayu; Gao, Yue; Méndez-Sánchez, Nahum; Qi, Xingshun (Frontiers in Medicine, 2024)
Purpose Chronic hepatitis B (CHB) and fatty liver disease (FLD) are common chronic liver diseases, both of which can progress to advanced liver diseases with poor outcome. However, it remains controversial whether the presence of FLD aggravates the disease severity of CHB patients. Patients and methods All consecutive outpatients who were diagnosed with CHB at our department between March 1, 2021 and September 30, 2023 were retrospectively screened. They were divided into FLD and non-FLD groups. Liver function parameters and non-invasive indicators of liver fibrosis, including liver stiffness measurement (LSM) value, fibrosis-4 index (FIB-4) score, and aspartate aminotransferase to platelet ratio index (APRI) score, were compared between the two groups. Subgroups analyses were performed in HBeAg-positive, HBeAb-positive, HBV DNA > 10 IU/mL, mild FLD, and moderate/severe FLD patients. Results Overall, 201 CHB patients were included, of whom 76 (37.81%) had FLD. In the overall analyses, CHB patients with FLD had a significantly higher alanine aminotransferase (ALT) (47.04 ± 53.28 vs. 32.95 ± 35.10, p = 0.003) than those without FLD, but there was no significant difference in the LSM value (7.79 ± 5.16 vs. 8.19 ± 4.99, p = 0.508), FIB-4 score (1.13 ± 0.75 vs. 1.28 ± 0.99, p = 0.679), and APRI score (0.41 ± 0.46 vs. 0.36 ± 0.47, p = 0.535) between CHB patients with and without FLD. The above-mentioned statistical results in all subgroup analyses were nearly consistent with those in the overall analyses. Conclusion FLD may intensify abnormal liver function reflected by increased ALT level in CHB patients, but not influence the progression of liver fibrosis.